Exercise type influences the effect of an acute bout of exercise on hippocampal neuronal activation in mice. (13th July 2022) - Tsuchida, Ryuki; Yamaguchi, Taisei; Funabashi, Daisuke; Koumi, Yusuke; Kita, Ichiro; Nishijima, Takeshi
Highlights: Hippocampal neuronal activation differs with exercise type of similar intensity. Mouse hippocampal activity is activated more by treadmill than by rotarod exercise. Exercise type is a key factor influencing exercise effects on the hippocampus. Abstract: The effects of exercise on the hippocampus depend on exercise conditions. Exercise intensity is thought to be a dominant factor that influences the effects of exercise on the hippocampus; however, it is uncertain whether the type of exercise influences its effectiveness. This study investigated whether the effect of an acute bout of exercise on hippocampal neuronal activation differs between two different types of exercise: treadmill and rotarod exercise. The intensities of both exercises were matched at just below the lactate threshold (LT), based on blood lactate concentration. Immunohistochemical examination of c-Fos, a marker of neuronal activation, revealed that treadmill exercise at 15 m/min (T15) significantly increased c-Fos expression in all subfields of the hippocampus (dentate gyrus DG, CA1, CA3), but rotarod exercise at 30 rpm (R30) did not, as compared with the respective control groups. These results demonstrate that moderate treadmill exercise more efficiently evokes hippocampal neuronal activation than does intensity-matched rotarod exercise. This suggests that exercise type is another important factor affecting the effects of exercise on the hippocampus.